2017
DOI: 10.14814/phy2.13307
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the autophagy system during chronic contractile activity-induced muscle adaptations

Abstract: Skeletal muscle is adaptable to exercise stimuli via the upregulation of mitochondrial biogenesis, and recent studies have suggested that autophagy also plays a role in exercise‐induced muscle adaptations. However, it is still obscure how muscle regulates autophagy over the time course of training adaptations. This study examined the expression of autophagic proteins in skeletal muscle of rats exposed to chronic contractile activity (CCA; 6 h/day, 9V, 10 Hz continuous, 0.1 msec pulse duration) for 1, 3, and 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
(108 reference statements)
5
31
0
Order By: Relevance
“…We examined markers of the lysosome in young and aged conditions, and also with CCA. In muscle of young animals, we have previously observed that CCA leads to an early adaptive increase in lysosomal markers, indicative of organelle biogenesis prior to mitochondrial adaptations (Kim & Hood, 2017). In the current study, we observed a CCA-induced increase in LAMP-1, supporting this increase in the capacity of muscle with respect to the terminal step of autophagy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We examined markers of the lysosome in young and aged conditions, and also with CCA. In muscle of young animals, we have previously observed that CCA leads to an early adaptive increase in lysosomal markers, indicative of organelle biogenesis prior to mitochondrial adaptations (Kim & Hood, 2017). In the current study, we observed a CCA-induced increase in LAMP-1, supporting this increase in the capacity of muscle with respect to the terminal step of autophagy.…”
Section: Discussionmentioning
confidence: 97%
“…; Mejías‐Peña et al . ; Kim & Hood, ). He and colleagues () observed a decreased association of Beclin 1 with Bcl‐2 within 30 min of acute exercise, despite a rise in total protein levels of Beclin 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They contain pHdependent enzymes for the breakdown of macromolecules and organelles. They also possess a number of lysosomeassociated membrane proteins (LAMPs) that are involved in autophagosome-lysosome fusion [14,26,28,49,56]. Lysosomal permeases and transporters then export amino acids and other by-products of degradation back out to the cytoplasm, where they can be re-used for building macromolecules or for metabolism ( Fig.…”
Section: General Autophagy Pathwaymentioning
confidence: 99%
“…It is well known that exercise has multiple beneficial health effects. Engaging in regular exercise facilitates an improvement in glucose homeostasis, cardiovascular health, the maintenance of muscle mass, and can help reduce complications that occur with aging [2,6,19,26,28,43,57]. On a molecular level, regular exercise exerts favorable effects on bioenergetics and nutrient delivery and uptake, which largely occur due to the accumulated adaptation of muscle in response to individual acute exercise bouts [18,19,48].…”
Section: Effect Of Acute Endurance Exercise On Mitophagymentioning
confidence: 99%